Imam Al-Qudduri’s Responses to the Opponents Arguments Based on the Verses of the Rulings in His Book Al-Tajreed, in the Chapters of Al Hajer and AL Wassia (A Comparative Jurisprudential Study) - Hussein, Mohammed Salman; Al-Mohammadi, Hajar Qutaiba Ghazi (Journal of Posthumanism, 2025)
The study aims to shed light on Imam al-Quduri's responses to the inference of violators of the verses of rulings in the chapters of Al-Hijr and Al-Wasiyyah (a comparative jurisprudential study). The verses of rulings, from which jurists derive the provisions of Sharia, hold a high rank among the Sharia sciences. This research seeks to clarify Imam al-Quduri's answers to the inference of violators of the verses of rulings in the chapters of Al-Hijr and Al-Wasiyyah. We have collected evidence from the eight major Islamic legal schools: the Hanafi, Maliki, Shafi'i, Hanbali, Zahiri, Ja'fari, Zaidi, and Ibadi schools. The research includes jurisprudential texts from the Hanafi and Shafi'i schools, despite the scarcity of scientific research on these topics, despite their abundance in the books of the two schools. We have made every effort to explain the evidence in all doctrines and to clarify the opinion of each doctrine on the most important issues where disputes occurred between them in the branches of jurisprudence, while studying the evidence and responding to the evidence of the other doctrines. This research aims to honestly express the spirit of tolerance and peaceful scientific discussion among all doctrines of jurisprudence, a hallmark of Muslim jurists. This is evident when Al-Qaduri addresses the Shafi'i and his companions, avoiding the use of violent or satirical language in response to them while recounting their evidence.